'Copper and solar': the gendered politics of service delivery in Solomon Islands. Issue 4 (3rd April 2022) - Baker, Kerryn
Abstract: Clientelism, and how clientelist political systems evolve over time, is of enduring interest to scholars of politics. The rise of constituency development funds (CDFs), especially in countries where they have come to represent a significant proportion of the government budget, complicates these dynamics, with some arguing their influence in Melanesia has prompted the emergence of a distinct form of statehood. But where do women fit into CDF politics, and this new form of statehood? This article introduces a gendered lens to the emerging literature on CDFs, using a case study of an incumbent woman member of parliament's campaign for re-election in Solomon Islands. It finds that changing political dynamics in Solomon Islands have not challenged the male dominance of the political space; there are, however, entry points for well-positioned women to gain a political foothold in the new Melanesian state. These findings suggest new avenues for future research, incorporating theories of gender and politics with the emerging literature on CDFs.